Programs Improvement and Sales Stimulation at the Enterprise - Prischepa, N.P.; Putintsev, A.V. (Економічний вісник Донбасу, 2013)
The article deals with one of the most actual problem of management practice - the problem of marketing programs improvement and sales stimulation at the enterprise. The article is devoted to solving theoretical and practical issues of sales promotion at the enterprise. The management approaches to stimulate sales at the enterprise are determined. The organizational structures of sales promotion and sales stimulation methods used at the enterprise are considered. Recommendations concerning management approaches to stimulate sales at the enterprise are provided.